Influence of e-Content Based Coaching on Selected Fundamental Skills in Field Hockey - M. Suresh Kumar, R. Kalidasan, K. Ivin Jabakumar* (Recent Research in Science and Technology, 2010)
<span style="line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; color: black; font-size: 10pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">The purpose of the study was to examine the influence of e-content based coaching on selected fundamental skills in Field Hockey. To achieve the purpose of this study 30 male under graduate students from Meenatchi Ramasamy group of institutions, Thathanur, Tamilnadu, India were selected as subjects and their age ranged between 17 and 20 years. The study was formulated as a true random group design, consisting of a pre-test and post-test. The subjects were randomly assigned to two equal groups of fifteen each and named as Group â€˜Aâ€™ and Group â€˜Bâ€™. Group â€˜Aâ€™ underwent teaching & coaching with e-content package and Group â€˜Bâ€™ undergone teaching & coaching without e-content package. The teaching & coaching with e-content group were shown the content developed electronically by the investigators and the other group was given teaching & coaching only in the field. Both the groups undergone respective schedule for six weeks on alternate days. Teaching & coaching session in the field lasted for 60 minutes and e-content schedule was meted out for 20 minutes. The fundamental skills namely straight hit, wrong foot hit, straight push, wrong foot push, straight flick, wrong foot flick and scoop in Hockey were selected as variables. The subjective rating was done by three qualified coaches on each skill selected in this study. The rating was done on 10 points scale by each coach and average on each skill was taken as individual score. Analysis of covariance was used, where the final means were adjusted for differences in the initial means, and the adjusted means were tested for significance. From the analysis of data it was found that the teaching & coaching combined with e-content package group showed significant improvement on all selected fundamental skills in Field Hockey.